New Approaches to Language Testing - Ingram, D. E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
The role of different types of testing instruments in second language programs is discussed. Knowledge-based tests, including discrete-point and integrative tests are contrasted with direct tests, including the Foreign Service Institute Scale and the Australian Second Language Proficiency Ratings (ASLPR). The ASLPR is described in detail in terms of its development, levels, tasks, parameters, uses, and formal trials. The ASLPR was originally developed to measure the proficiency of adult English as second language learners and then expanded for use with adolescents and other languages. The ASLPR is valid, reliable, and suitable for the measurement of general proficiency, while other instruments may be more appropriate for various other testing objectives. Other uses for language proficiency tests in second language programs include obtaining a quick group measure of proficiency, measuring special purpose proficiency; measuring summative evaluation of course attainment; and for student placement, diagnosis of student strengths and weaknesses, program evaluation, and test validation. (RW)
ERIC Note: Paper presented at the Annual National Languages Conference of the Australian Federation of Modern Language Teachers Associations (4th, Perth, Australia, September 3-6, 1982).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Adults; Comparative Analysis; English (Second Language); Evaluation Methods; Foreign Countries; Language Proficiency; Language Tests; Second Language Learning; Second Language Programs; Secondary Education; Student Evaluation; Test Reliability; Test Validity; Testing; Australian Second Language Proficiency Ratings; Australia -- Foreign Service Institute Interview; Speeches/Meeting Papers; Guides, Non-Classroom.